Pengaruh Kompetensi Profesional Guru Terhadap Kreativitas Siswa Pada Mata Pelajaran Tarikh Islam - Ahmad Rifqi Jundullah; Bahrum Subagiya; Noor Isna Alfaien (CV. ITTC INDONESIA, 2025)
Teachers' professional competence plays an important role in creating a meaningful learning process and influences the development of students' creativity. This study aims to determine the level of teachers' professional competence, the level of students' creativity, and the influence of teachers' professional competence on students' creativity in the subject of Islamic History at the Darussalam Ciomas Bogor Islamic Boarding School. This study uses a quantitative approach with a survey method. Data were obtained through questionnaires distributed to 100 students. The instruments were tested using validity and reliability tests, and analyzed using prerequisite tests (normality and linearity), Pearson correlation tests, and simple linear regression tests. The results of the study showed that teachers' professional competence and students' creativity were in the high category. There is a significant influence between teacher professional competence on student creativity with a significance value of 0.000 and a correlation coefficient (r) of 0.644. The determination coefficient value (R²) of 0.415 indicates that 41.5% of the variation in student creativity is influenced by teacher professional competence. It can be concluded that the higher the teacher's professional competence, the higher the student's creativity in learning Islamic History. Therefore, increasing teacher competence is an important factor in supporting innovative and creative learning processes in Islamic boarding schools